IMPROVING EARLY CHILDHOOD STUDENTS’ ENGLISH VOCABULARY BY USING ANIMAL POP UP SLIDE MEDIA IN TK AISYIYAH DOLOPO - Fahad Sandi Agassy; Bambang Harmanto; Niken Reti Indriastuti (EDUPEDIA, 2020)
Young learners can be defined as children in age ranging from five or six years old who are attending elementary school to twelve years old.  In this research the researcher chose to teach vocabulary in TK (kindergarten) Aisyiyah Dolopo. The reason for choosing to teach vocabulary is because vocabulary is one of the important elements in language. The researcher focuses on teaching vocabulary words to the young learners. The researcher used pop up slide book to improve students’ vocabulary. The pop up slide book is a book which shows three dimensional pictures when the pull or trigger is pulled. The name pop up slide book is originated from the term “Slide” which means “to move smoothly along a surface”. The name slide was added by the researcher as the new variant of pop up book. The method for this research was Classroom Action Research which took two cycles. This research method was conducted to know the problems inside the classroom thus the solution can be found. The goal of this research is to make children learn English through pop up slide book. The instruments used in this research were observation, interview and test. The research results based on the implementation of popup animal slide media in TK Aisyiyah Dolopo Madiun showed that in cycle 1 up to cycle 2 the implementation of pop up slide book was able to improve students’ score. In the first cycle many students achieved score 70 and in the second observation their score were above 80. The highest score was 100 for the test in cycle 2. The interview result showed that 100% of the students liked the pop up slide book with the animal poster. In the first interview cycle, 87% of students were afraid to learn English but in the second interview cycle, 100% of students could speak English comfortably without hesitation. Moreover from the observation in first cycle only 46% students who were excited to learn with pop up book, but in the second cycle 90% of students were excited to learn English during lesson using pop up slide book. It means that pop up Slide Book as teaching media could successfully improve students’ vocabulary. Keywords: Kindergarten, Pop Up Slide Book, Vocabulary